Barbados : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
This 2002 Article IV Consultation highlights that eight consecutive years of growth in Barbados ended in 2001 as real GDP contracted by 2 3/4 percent, owing mainly to the adverse impact on tourism of the global economic slowdown and the September 11 terrorist attacks, as well as continuing declines in agriculture and manufacturing output. To lessen the impact of the September 11 attacks, the authorities implemented a national emergency program in the fourth quarter of 2001. Broad money grew by 5 1\2 percent in 2001, reflecting capital inflows and an increase in international reserves.